Chinese as a Second and Foreign Language Education Pedagogy and Psychology - Cai, Qiao Yu (Springer Singapore, 2018)
This book presents key issues in the teaching of Chinese as a second or foreign language (TCSL or TCFL). It investigates how multimedia can help to assist TCSL/TCFL and explores practical effects of multimedia-assisted teaching at secondary schools in the Philippines. It addresses the psychology of TCSL/TCFL and discusses various recurring foreign graduate students concerns when learning academic Chinese in graduate institutes in Taiwan. It examines issues of educational assessment and testing, analyzing the validity of a self-made placement test for an immigrant Chinese program, as well as the psychological characteristics of adult learners and their implications for immigrant Chinese curriculum design. As foreign learners of Chinese grow exponentially, this cutting edge read conceptualizes the educational philosophy of TCSL/TCFL as a distinctive discipline.